2017
DOI: 10.1155/2017/1325754
|View full text |Cite
|
Sign up to set email alerts
|

Decolourisation Capabilities of Ligninolytic Enzymes Produced byMarasmius cladophyllusUMAS MS8 on Remazol Brilliant Blue R and Other Azo Dyes

Abstract: Marasmius cladophyllus was examined for its ability to degradatively decolourise the recalcitrant dye Remazol Brilliant Blue R (RBBR) and screened for the production of ligninolytic enzymes using specific substrates. Monitoring dye decolourisation by the decrease in absorbance ratio of A592/A500 shows that the decolourisation of RBBR dye was associated with the dye degradation. Marasmius cladophyllus produces laccase and lignin peroxidase in glucose minimal liquid medium containing RBBR. Both enzyme activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…strain produces a color change from dark blue before to light color of liquid culture medium after 7 d of incubation. The decolorization ability of ligninolytic enzymes produced by Marasmius cladophyllus can be proposed for the bioremediation of RBBR dye contained in the textile industry wastewater [ 44 ]. The results ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…strain produces a color change from dark blue before to light color of liquid culture medium after 7 d of incubation. The decolorization ability of ligninolytic enzymes produced by Marasmius cladophyllus can be proposed for the bioremediation of RBBR dye contained in the textile industry wastewater [ 44 ]. The results ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors reported that laccase plays the primary role in Orange G decolorization, while MnP production is more significant for RBBR decolorization [ 20 , 69 , 86 , 87 , 88 ]; nevertheless, others consider MnP to be essential for both azo and anthraquinone dye decolorization [ 31 , 89 , 90 , 91 ]. On the other hand, some authors declared the crucial role of laccase in the decolorization of RBBR [ 62 , 67 , 68 ] or in the decolorization of both anthraquione and azo dyes [ 28 , 49 ]. Although it is widely known that the ligninolytic enzymes laccase and MnP produced by saprotrophic fungi play a crucial role in the degradation of various xenobiotics, including dyes [ 92 ], the process of their degradation is more complicated and many other factors (different mediators, radicals, hydrogen peroxide, other oxidative enzymes, and so on) participate in it [ 7 , 17 , 18 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marasmius cladophyllus were demonstrated by Sing et al (2017). In their study, Marasmius cladophyllus produced a laccase enzyme that able to degraded those recalcitrant dyes.…”
Section: The Decolourisation Studies Of Anthraquinone Dyes Bymentioning
confidence: 99%
“…Some species of fungi also form a mutualistic symbiosis with plant roots and form mycorrhiza structures (Pointing et al, 2005;Lehto & Zwiazek, 2011;Lenoir et al, 2016;Guerrero-galán et al, 2019). Besides, several species of fungi are also Doi: https://doi.org/10.22236/j.bes/515326 ISSN: 2614-1558 | 31 applied for biotechnology purposes, and the results of its applications are developed extensively in several industries areas such as food, agriculture, textile, medicine, and wastewater treatment (Sing et al, 2017;Anita et al, 2019;Hyde et al, 2019). As a eukaryotes organism, fungi can be found in both macroscopic and microscopic forms.…”
Section: Introductionmentioning
confidence: 99%